Knowledge coproduction: panacea or placebo? Lessons from an emerging policy partnership. Issue 2 (3rd April 2022) - Reddel, Tim; Ball, Sarah
Abstract: Governments across the globe have expressed their interest in forms of codesign and coproduction as a useful tool for crafting policy solutions. Genuine relationships between partners are seen as an important way to build meaningful and lasting impact for policy. One area of interest in this space has been on how researchers and policymakers can work better together to design and produce more evidence-based policies. For many practitioners and researchers, knowledge coproduction is presented as a panacea to the ongoing challenges of research translation. It is positioned as assisting in building more meaningful, trusting relationships which, in turn, support the development of more effective policy solutions. Using the insider experience of a coproduced government project in Queensland, Australia, this paper reflects on the realities and tensions between this idealism associated with policy co-production methodologies and the ongoing messiness of public policy practice. Beginning with an overview of the literature on coproduction, followed by a brief introduction to the case and the method used, the paper concludes by highlighting the strengths, facilitators and benefits of the approach while raising questions about whether coproduction is a panacea to research translation concerns or a placebo. The answer, we argue, lies more in how success is defined than any concrete solution.